Karakteristik Konsentrat Protein Biji Labu Kuning (Cucurbita moschata ex poir) pada Berbagai pH Pelarut - Ni Putu Desva Mardany; Ni Luh Ari Yusasrini; Ni Nyoman Puspawati (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Abstract Protein concentrate is a product of protein isolation made from food ingredients and is known to have high protein content. Pumpkin seeds (Cucurbita moschata ex poir) are vegetable waste that have a fairly high protein content which is known to be used as a protein concentrate. Factors such as solvent pH in the manufacture of protein concentrate are also important to consider in order to obtain optimum protein content from pumpkin seeds. This study aims to determine the effect of solvent pH on the characteristics of pumpkin seed protein concentrate and determine the right solvent pH in protein isolation so that it can produce pumpkin seed protein concentrate with the best characteristics. The design used in this study was a Completely Randomized Design consisting of 6 levels of solvent pH treatment, namely pH 7, pH 8, pH 9, pH 10, pH 11 and pH 12. The data obtained were analyzed using Analysis of Variance (ANOVA) and treatments that influenced the parameters were continued with the Duncan Multiple Range Test (DMRT). The results showed that the pH of the solvent had a significant effect (P<0.05) on the yield, water content, ash content, protein content, fat content and brightness. The best protein concentrate treatment was obtained at pH 11 (P5) with characteristics of 29.26% yield; 8.85% water content; 1.75% ash content; 67.4% protein content; 17.52% fat content and obtained 15 types of amino acids with arginine as the highest essential amino acid of 170.96 ppm and glutamate as the highest non-essential amino acid of 99.65 ppm. Keywords: Pumpkin Seeds, Protein Concentrate, Solvent pH Abstrak Konsentrat protein merupakan produk hasil isolasi protein yang terbuat dari bahan pangan dan diketahui memiliki kandungan protein tinggi. Biji labu kuning (Cucurbita moschata ex poir) merupakan limbah nabati yang memiliki kandungan protein cukup tinggi yang diketahui dapat dimanfaatkan sebagai konsentrat protein. Faktor seperti pH pelarut alam pembuatan konsentrat protein juga penting diperhatikan untuk memperoleh kandungan protein dari biji labu kuning secara optimum. Penelitian ini bertujuan untuk mengetahui pengaruh pH pelarut terhadap karakteristik konsentrat protein biji labu kuning dan menentukan pH pelarut yang tepat dalam isolasi protein sehingga dapat menghasilkan konsentrat protein biji labu kuning dengan karakteristik terbaik. Rancangan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap yang terdiri dari 6 taraf perlakuan pH pelarut, yaitu pH 7, pH 8, pH 9, pH 10, pH 11 dan pH 12. Data yang diperoleh dianalisis menggunakan analisis ragam (ANOVA) dan perlakuan yang berpengaruh terhadap parameter dilanjutkan dengan uji berjarak ganda Duncan (DMRT). Hasil penelitian menunjukkan bahwa pH pelarut berpengaruh nyata (P<0,01) terhadap rendemen, kadar air, kadar abu, kadar protein, kadar lemak dan kecerahan. Perlakuan konsentrat protein terbaik diperoleh pada perlakuan pH 11 (P5) dengan karakteristik rendemen 29,26%; kadar air 8,85%; kadar abu 1,75%; kadar protein 67,4%; kadar lemak 17,52% dan memperoleh 15 jenis asam amino dengan arginin sebagai asam amino esensial tertinggi sebesar 170,96 ppm dan glutamat sebagai asam amino non esensial tertinggi sebesar 99,65 ppm. Kata Kunci: Biji Labu Kuning, Konsentrat Protein, pH Pelarut